Examination of the relationship between perceived freedom levels in leisure time and multidimensional leadership orientations of individuals engaged in nature sports as a recreational activity - Koç, Kenan; Yüce, Mustafa Soner; Ulucan, Hakkı; Serarslan, Mustafa Zahit; Usuflu, Oğulcan; Kir, Sevim; Kirik, Erdal (Frontiers in Psychology, 2025)
IntroductionThe purpose of this study is to examine the relationship between perceived freedom in leisure and multifaceted leadership orientations among individuals engaged in recreational nature sports residing in various provinces of the Central Anatolia region.MethodsIn this study, a quantitative research method was used. The sample consisted of 633 randomly selected volunteers from Kayseri, Kýrşehir, and Nevşehir. Data collection instruments included the “Multifaceted Leadership Orientations Scale”, “Perceived Freedom in Leisure Scale”, and demographic information form. Participants' personal information, inventory scores, and factor scores were presented using frequency (f) and percentage (%) values. For comparing scale scores, independent t-test statistics were used for gender and marital status variables, while one-way analysis of variance (LSD) was employed for age, educational status, sports discipline, duration of engagement in nature sports, and welfare level comparisons. Pearson correlation analysis (r) was applied to determine the relationship between the scores obtained from the scales.ResultsThe research findings indicate that individuals participating in recreational nature sports activities exhibit high levels of perceived freedom in leisure and average levels of leadership orientation. On the other hand, analysis of various variables revealed significant differences between perceived freedom in leisure time and marital status, sport discipline, and years of participation, as well as between the some sub-dimensions of multifaceted leadership orientations and gender, marital status, education level, age, sport discipline, years of participation, and welfare level.DiscussionThe correlation analysis revealed a strong positive relationship between perceived freedom in leisure levels and multifaceted leadership orientations. This positive correlation is thought to stem from individuals' desire to prioritize their own wishes, emotions, and ideas to feel free during their leisure time.